2004
DOI: 10.1243/030932404773123877
|View full text |Cite
|
Sign up to set email alerts
|

Flexural behaviour of a polyvinyl chloride-lined glass-reinforced plastic composite multi-mitred pipe bend subjected to combined loads: A comparative finite element analysis and experimental case study

Abstract: case study pipe bend subjected to combined loads: A comparative finite element analysis and experimental Flexural behaviour of a polyvinyl chloride-lined glass-reinforced plastic composite multi-mitred Published by: http://www.sagepublications.com On behalf of: Institution of Mechanical Engineers can be found at: The Journal of Strain Analysis for Engineering Design Additional services and information for Abstract:The exural behaviour of a glass-reinforced plastic (GR P) multi-mitred pipe bend (MM PB) subjecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Al. [9] which ends with a good agreement between the experimental and the finite element analysis on a composite tubular structure subjected to a combined loading. The elbow in its geometric configuration will cause a variation of stress along its intrados and the extrados from where the analytical solutions that are possible to be implemented [10].…”
Section: Introductionsupporting
confidence: 62%
“…Al. [9] which ends with a good agreement between the experimental and the finite element analysis on a composite tubular structure subjected to a combined loading. The elbow in its geometric configuration will cause a variation of stress along its intrados and the extrados from where the analytical solutions that are possible to be implemented [10].…”
Section: Introductionsupporting
confidence: 62%
“…The component was tested as a three-dimensional model using 8-node element, where pressure was given as an input to study the shear and peel stresses. Kochekseraii et al [234] analysed the glass fibre reinforced with polyvinyl chloride pipe flexural behaviour, using the ABAQUS FE programme. The pipe was considered as the isoperimetric shell element and subjected to bending in the plane as well as internal pressure.…”
Section: Recent Advancements In Numerical Simulation On Frp Composite...mentioning
confidence: 99%
“…Babaii Kocheckseraii and Robinson [94] using both experiment and finite element analysis, examined the combined effects of pressure and IPB for a poly-vinyl chloride (PVC)-lined GRP multi-mitre. The authors concluded that only large-displacement finite element analysis is suitable for the practical design of bends subjected to combined internal pressure and IPB.…”
Section: Article In Pressmentioning
confidence: 99%
“…Ingenhousz [66], Hose [84], Kitching and Hose [85], Babaii Kochekseraii [83] and Babaii Kochekseraii and Robinson [94] conducted experiments on PVC-lined GRP multi-mitred bends. However, in all cases, the GRP lay-up was assumed to be quasi-isotropic.…”
Section: Anisotropy/orthotropymentioning
confidence: 99%